The Effect of Employer Branding and Digital Recruitment on Generation Z’s Job Application Intention: The Mediating Role of Candidate Experience - Ainiyah Aprelianingrum; Sagung Ayu Dwianjani Trisna Indraswari; Siti Mujanah; I Made Suparta (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The rapid development of digital technology has encouraged companies to adopt employer branding and digital recruitment strategies to attract Generation Z job applicants. This study aims to analyze the influence of employer branding and digital recruitment on job application intention through candidate experience as a mediating variable. This research employed a quantitative approach using Structural Equation Modeling-Partial Least Square (SEM-PLS). Data were collected through online questionnaires distributed to 115 Generation Z respondents in East Java and Bali who had experience applying for jobs. The results indicate that employer branding and digital recruitment have a positive and significant effect on candidate experience and job application intention. However, candidate experience does not significantly affect job application intention and is unable to mediate the relationship between employer branding and digital recruitment on job application intention. The findings indicate that employer branding and digital recruitment directly influence Generation Z's job application intention, whereas candidate experience does not function as a significant mediator. Therefore, organizations should prioritize strengthening employer branding and optimizing digital recruitment systems to attract Generation Z applicants.